TALENs Facilitate Single-step Seamless SDF Correction of F508del CFTR in Airway Epithelial Submucosal Gland Cell-derived CF-iPSCs - Shingo Suzuki; R Geoffrey Sargent; Beate Illek; Horst Fischer; Alaleh Esmaeili-Shandiz; Michael J Yezzi; Albert Lee; Yanu Yang; Soya Kim; Peter Renz; Zhongxia Qi; Jingwei Yu; et al. (Elsevier, 2016)
Cystic fibrosis (CF) is a recessive inherited disease associated with multiorgan damage that compromises epithelial and inflammatory cell function. Induced pluripotent stem cells (iPSCs) have significantly advanced the potential of developing a personalized cell-based therapy for diseases like CF by generating patient-specific stem cells that can be differentiated into cells that repair tissues damaged by disease pathology. The F508del mutation in airway epithelial cell-derived CF-iPSCs was corrected with small/short DNA fragments (SDFs) and sequence-specific TALENs. An allele-specific PCR, cyclic enrichment strategy gave ≃100-fold enrichment of the corrected CF-iPSCs after six enrichment cycles that facilitated isolation of corrected clones. The seamless SDF-based gene modification strategy used to correct the CF-iPSCs resulted in pluripotent cells that, when differentiated into endoderm/airway-like epithelial cells showed wild-type (wt) airway epithelial cell cAMP-dependent Cl ion transport or showed the appropriate cell-type characteristics when differentiated along mesoderm/hematopoietic inflammatory cell lineage pathways.